Lack of Racial Survival Differences in Metastatic Prostate Cancer in National Cancer Data Base (NCDB): A Different Finding Compared to Non-metastatic Disease - Vengaloor Thomas, Toms; Gordy, Xiaoshan Z.; Lirette, Seth T.; Albert, Ashley A.; Gordy, David P.; Vijayakumar, Srinivasan; Vijayakumar, Vani (Frontiers in Oncology, 2020)
Background: Inconsistent findings have been reported in the literature regarding racial differences in survival outcomes between African American and white patients with metastatic prostate cancer (mPCa). The current study utilized a national database to determine whether racial differences exist among the target population to address this inconsistency. Methods: This study retrospectively reviewed prostate cancer (PCa) patient data (N=1,319,225) from the National Cancer Database (NCDB). The data were divided into three groupings based on the metastatic status: (1) no metastasis (N=318,291) (2) bone metastasis (N=29,639) and (3) metastases to locations other than bone, such as brain, liver, or lung (N=952). Survival probabilities of African American and white PCa patients with bone metastasis were examined through parametric proportional hazards Weibull models and Bayesian survival analysis. These results were compared to patients with no metastasis or other types of metastases. Results: No statistically supported racial disparities were observed for African American and white men with bone metastasis (p=0.885). Similarly, there were no racial disparities in survival for those men suffering from other metastases (liver, lung, or brain). However, racial disparities in survival were observed among the two racial groups with non-metastatic PCa (p<0.001) or when metastasis status was not taken into account (p<0.001). The Bayesian analysis corroborates the finding. Conclusion: This research supports our previous findings and shows that there are no racial differences in survival outcomes between African American and white patients with mPCa. In contrast, racial disparities in the survival outcome continue to exist among non-metastatic PCa patients. Further research is warranted to explain this difference.